2017
DOI: 10.5897/ajmr2016.8384
|View full text |Cite
|
Sign up to set email alerts
|

A very high frequency of hepatitis B and C virus infections during an active screening campaign in Abidjan

Abstract: Viral hepatitis is a serious public health problem affecting billions of people globally. Limited information is available on this issue inCote d'Ivoire. The objectives of this study were to determine the prevalence and factors associated with hepatitis B virus (HBV) and hepatitis C virus (HCV) during an active screening campaign in Abidjan. A cross-sectional study was conducted at Pasteur Institute of Cote d'Ivoire from July 2015 to February 2016. The ethical clearance for this study was obtained from the Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 18 publications
2
3
4
Order By: Relevance
“…There was no statistically significant difference between viral infections and scarification marks (p > 0.05). Such was also reported in a similar study in Cote d'voire [12]. There was no statistically significant association between locality and the viral infections (p > 0.05).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…There was no statistically significant difference between viral infections and scarification marks (p > 0.05). Such was also reported in a similar study in Cote d'voire [12]. There was no statistically significant association between locality and the viral infections (p > 0.05).…”
Section: Discussionsupporting
confidence: 80%
“…, 7.9% in Abuja[11], 3.9% in Lagos[9] and 12.3% in Kano[10] among HIV patients. Similar studies from other countries found 30.9% in Cote d'voire[12], 6.0% in Kenya[7] 1.16% in Pakistan[13], 10.3% in Brazil[1]. These differences in prevalence might be as a result of geographical location, population and sensitivity of tests used for screening.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Viral hepatitis is also a serious public health concern that affects billions of people globally [16]. More than 240 million people have HBV globally, and the majority occur in developing countries [16,17], such as Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Viral hepatitis is also a serious public health concern that affects billions of people globally [16]. More than 240 million people have HBV globally, and the majority occur in developing countries [16,17], such as Nigeria. Of the total number of persons living with HIV, about 7.4% are co-infected with HBV while 1% of persons living with HBV are also infected with HIV [18].…”
Section: Introductionmentioning
confidence: 99%